Strategi Pengembangan Kecamatan Enrekang Berbasis Indeks Desa Membangun - Zalfa Salsabila; Irsyadi Siradjuddin; Nurfatimah Nurfatimah (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The implementation of village development has been regulated by the government throught Law No. 6/2014 on Villages. Article 78 of the Village Law states that village development is an activity that aims to improve the welfare and quality of life of the village community through the fulfillment of basic needs, the development of village facilities and infrastructure, and the development of the local economy through the sustainable use of resources.  To determine the target locus for alleviating underdeveloped villages, the government developed the Village Development Index (IDM), which serves as a map for village development. The IDM consists of the Social Resilience Index (IKS); Economic Resilience Index (IKE); and Environmental Resilience Index (IKL), which is a translation of the development needs set out in article 74 paragraph (2) of the Village Law. The Village Development Index is not only useful to determine the development status of each village, which is closely related to its characteristics, but can also be developed as an instrument for targeting village development. The purpose of this study was to determine the classification of village status and to determine the development strategy of village development in Enrekang Sub-district. The benefit of this research is as a reference for the local government in implementing village development programs in Enrekang District. The research methods used in this study are qualitative and quantitative methods with research locations located in 12 villages in Enrekang District, Enrekang Regency. The analysis technique used is Village Development Index Analysis and SWOT Analysis with data collection techniques namely observation, interviews, and questionnaires. The results of this study determine the classification of village status of 12 villages in Enrekang Sub-district and determine the strategy for developing village potential in Enrekang Sub-district.